Emotional Processing and Its Association to Somatic Symptom Change in Emotional Awareness and Expression Therapy for Somatic Symptom Disorder: A Preliminary Mediation Investigation - Maroti, Daniel; Ljótsson, Brjánn; Lumley, Mark A.; Schubiner, Howard; Hallberg, Henrik; Olsson, Per-Åke; Johansson, Robert (Frontiers in Psychology, 2021)
Objective: The aim of this study was to investigate emotional processing as a potential mediator in therapist-guided, internet-based Emotional Awareness and Expression Therapy (I-EAET) for somatic symptom disorder, using data from a previously published pilot study. Methods: Participants (N = 52) engaged in a 9-week I-EAET treatment. Before treatment and each week during treatment (i.e., 10 weekly measurements), emotional processing was assessed with the Emotional Processing Scale-25 (EPS-25), which contains five subscales, and somatic symptoms were assessed with the Patient Health Questionnaire-15 (PHQ-15). Results: Mediation analyses using linear mixed models showed that two EPS-25 subscales—Signs of Unprocessed Emotions and Impoverished Emotional Experience—were uniquely associated with somatic symptom reduction. The proportion of the mediated effect was 0.49, indicating that about half of the total association of the PHQ-15 with symptoms was accounted for by the two EPS-25 subscales. Conclusion: This preliminary mediation analysis suggests that improved emotional processing is associated with change in somatic symptoms in I-EAET. However, randomized controlled and comparison trials are needed to establish that I-EAET creates the change in emotional processing and that such changes are specific to I-EAET.